2019
DOI: 10.5505/eudfd.2019.49379
|View full text |Cite
|
Sign up to set email alerts
|

The rate of tobacco smoking among dental school students in Turkey

Abstract: Objectives: This survey aimed to investigate the attitudes of the first-and fifth-year Turkish dental school students towards tobacco and to determine the prevalence of those using various tobacco products. Materials & Methods: The survey was conducted between May 1 and June 30, 2018 and the first-and fifth-year students were from eleven dental schools located in different regions of Turkey. Data were tested statistically using Statistical Package for Social Science (SPSS) program. Results: A total of 1228 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…[20][21][22] Another study conducted in Turkey reported that 62.0 % of the participants had inhaled cigarette smoke at least once, even though the median number of active smokers was 37.9%. 23 These rates of previous experience and current usage are similar to those found in our current study. In our research, 75.5 % had tried cigarettes at least once and 36.9% were current users, with the majority of smokers claiming that peers had influenced their decision (32.0%).…”
Section: Discussionsupporting
confidence: 90%
“…[20][21][22] Another study conducted in Turkey reported that 62.0 % of the participants had inhaled cigarette smoke at least once, even though the median number of active smokers was 37.9%. 23 These rates of previous experience and current usage are similar to those found in our current study. In our research, 75.5 % had tried cigarettes at least once and 36.9% were current users, with the majority of smokers claiming that peers had influenced their decision (32.0%).…”
Section: Discussionsupporting
confidence: 90%
“…Since most of the early signs of tobacco consumption are observed in the oral cavity, dental providers are imposed with a critical responsibility of reducing the risk of tobacco‐related disorders through counselling and to be a good role model for society by leading a tobacco‐free lifestyle 37,38 . In the present study, although the defined smoking rate for preclinical (21.91%) and clinical students (23.88%) was relatively lower than the rates reported in similar recent studies (29.9% and 37.96%), 37,38 it is higher than the smoking rate of the general population (16.7% males, 13.6% females) 39 . This finding is similar to previous studies that reported a high prevalence of tobacco use amongst healthcare professionals and an increased prevalence of smoking amongst undergraduate students from the first year to the upper grades 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is associated with significant chronic disorders, such as periodontal diseases, oral cavity, larynx and lung cancers, diabetes and cardiovascular diseases 35,36 . Since most of the early signs of tobacco consumption are observed in the oral cavity, dental providers are imposed with a critical responsibility of reducing the risk of tobacco‐related disorders through counselling and to be a good role model for society by leading a tobacco‐free lifestyle 37,38 . In the present study, although the defined smoking rate for preclinical (21.91%) and clinical students (23.88%) was relatively lower than the rates reported in similar recent studies (29.9% and 37.96%), 37,38 it is higher than the smoking rate of the general population (16.7% males, 13.6% females) 39 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation